Community supervision orders for the mentally ill: Mental health professionals' attitudes - Burns, T (Informa Healthcare, 1995)
Considerable national debate exists about the need for some form of compulsory supervision or treatment for mentally disordered individuals in the community and a recent Government review has proposed a new power of Supervised Discharge. Prior to this, a survey was undertaken in the London area of psychiatrists, community psychiatric nurses and approved social workers (ASWs). Their knowledge of, and attitudes towards, various forms of proposal were obtained. There were clear professional differences in willingness to use such powers, with psychiatrists the most enthusiastic. The Royal College of Psychiatrists' proposal was the best understood and most favoured by all three groups. Only ASWs considered extension of guardianship order a viable alternative and they placed it third. The commonest reservations expressed were that compulsory supervision would scare patients off or be used as a substitute for properly resourced services. Psychiatrists were asked to indicate the number and diagnoses of patients they considered suitable for compulsory supervision. Over 70% of patients recommended suffered from schizophrenic disorders and 20% from affective psychoses. Their number ranged from 0-15 per team with an average of 2.38. The total adjusted figure for South West Thames was 195 patients, which would suggest just over three thousand patients in England and Wales. © 1995 Informa UK Ltd All rights reserved: reproduction in whole or part not permitted.